A Linguistic Error Analysis of Google Translate Translation Result From Bahasa Indonesia To English - Azwar Fadlan; Ichsan Ichsan (LPPM Universitas Bumigora Mataram, 2022)
This study discusses the analysis of linguistic errors resulting from the translation of Indonesian text into English using Google Translate. The linguistic errors in question are errors at the morphological, syntactic, and semantic levels. The purpose of this research is to present the results of the analysis of linguistic errors in the translation of Indonesian texts into English and to describe examples of linguistic errors, with the hope that the use of Google Translate can provide complete and acceptable translation results in accordance with linguistic rules. The method used in this study is a descriptive qualitative method in which the researcher analyses linguistic errors in the Indonesian text which is translated into English. The subject of this research involved 13 students from the English Education Study Program at the Faculty of Teacher Training and Education, Pohuwato University. Research findings show that there are two linguistic errors found, which are classified into syntactic and morphological errors.